National Lampoon's vacation ; National Lampoon's European vacation [videorecording (DVD)] - Simmons, Matty; Hughes, John, 1950-2009; Heckerling, Amy; Ramis, Harold; Klane, Robert, 1941-2023; Chase, Chevy; D'Angelo, Beverly; Coca, Imogene; Quaid, Randy, 1950-; Candy, John; Brinkley, Christie; Burns, Ralph; et al. (Warner Home Video, 2006)
National Lampoon's vacation: When a typical American family takes a cross-country vacation, it can only mean one thing: total disaster.